2015
DOI: 10.1371/journal.pone.0137299
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Accuracy of Cervical Cancer Screening Using a Self-Collected Tampon for HPV Messenger-RNA Testing among HIV-Infected Women in South Africa

Abstract: BackgroundHIV increases women’s risk for high-risk human papillomavirus (hrHPV) infection and invasive cervical cancer. South Africa has a high HIV prevalence but low cervical cancer screening coverage. Self-collection of cervical specimens and hrHPV testing, including hrHPV messenger-RNA (mRNA) testing, are methods aimed at increasing screening rates. However, data are limited on the acceptability and accuracy of tampon-based self-collection for hrHPV mRNA testing in HIV-infected women.MethodsWe recruited 325… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 28 publications
(37 reference statements)
3
74
1
Order By: Relevance
“…The present results were comparable to those from three similar cross-sectional studies that compared hrHPV-RNA detection in self-and physician-collected specimens among women in South Africa (κ=0.54), Nepal (κ=0.62), and Canada (κ=0.63). [14][15][16] The accuracy of hrHPV-RNA testing for detection of HSIL+ was similar for self-and physician-collected specimens over 12 months.…”
Section: Discussionmentioning
confidence: 85%
“…The present results were comparable to those from three similar cross-sectional studies that compared hrHPV-RNA detection in self-and physician-collected specimens among women in South Africa (κ=0.54), Nepal (κ=0.62), and Canada (κ=0.63). [14][15][16] The accuracy of hrHPV-RNA testing for detection of HSIL+ was similar for self-and physician-collected specimens over 12 months.…”
Section: Discussionmentioning
confidence: 85%
“…In total, 13 of the included studies were cohort studies, and 8 reported cross‐sectional findings in eligible populations.…”
Section: Resultsmentioning
confidence: 99%
“…The non‐randomized studies recruited populations with different characteristics. For example, Viviano et al., Adamson et al., and Rositch et al . enrolled women with HIV in a cohort study; Toliman et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of self-collection in low-and middleincome countries (LMIC) have not evaluated actual patient preferences, as measured by screening adherence. Rather, studies in LMICs have had enrolled, consenting women undergo self-collection with or without also getting a provider-collected specimen and then relied on questionnaires and interviews to understand the acceptability/ patient preferences for self-collection (11)(12)(13)(14). As an exception, in a randomized trial of almost 6,000 women in Argentina, women offered self-collected sampling were 4-fold more likely to complete screening compared with those who were offered clinic-based provider-collected sampling for cytology (86% vs. 20%, respectively; ref.…”
Section: Introductionmentioning
confidence: 99%